Field Grafting and Budding in Teak (Tectona grandis L.f.) - Rawat, M. S.; Kedharnath, S. (Indian Forester, 1968)
In the genetic improvement of forest trees vegetative propagation methods particularly grafting, assume great importance in that it enables the tree breeder to assemble the select clones in the seed orchard. In teak, grafting and budding trials were carried out in the field to find out the time when the ’take’ would be the highest and also to assess the relative merits of the two methods. During the months of April and May in Dehra Dun, the ’take’ in budding and grafting was observed to be very high. Both these methods are recommended for use in the establishment of seed orchards in teak.